Deformation characteristics and constitutive model of seafloor massive sulfides - Hu, Jian-hua; Liu, Shao-jun; Zhang, Rui-qiang; Hu, Qiong (Journal of Central South University, 2017)
Deformation characteristics and constitutive model of seafloor massive sulfide (SMS) were selected as the research object. Uniaxial/triaxial compression test were carried out on the mineral samples, and the deformation characteristics of specimens under various conditions were studied. According to characteristics of the mineral, a new three stages constitutive equation was proposed. The conclusions are as follows: The axial strain, peak strain and maximum strength of seafloor massive sulfide increase with the confining pressure. The elastic modulus of the metal sulfide samples is decreased sharply with the increase of confining pressure. According to characteristics of seafloor massive sulfide, the constitutive equation is divided into three parts, the comparison between theoretical curves and experimental data shows that both of them are in good agreement, which also proves the correctness of the constitutive equation for uniaxial compression.